2020
DOI: 10.21203/rs.3.rs-38321/v5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic on Dental Practice in Iran: A questionnaire-based report

Abstract: Background: The highly contagious nature of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV2), besides the fact that dental procedures commonly generate blood and saliva droplets that could lead to the contagion have resulted in the closure of many dental clinics. In the present study, we aimed to evaluate the impact of coronavirus disease 2019 (COVID-19) pandemic on dental practice by conducting an online questionnaire among the Iranian dental practitioners and finding their perspectives on the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
(14 reference statements)
1
8
0
1
Order By: Relevance
“…The main presenting symptoms of our participants have shown concordance with other studies from different countries [23][24][25][26]. In addition, the mean duration of symptoms is similar to previous studies [17,18].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The main presenting symptoms of our participants have shown concordance with other studies from different countries [23][24][25][26]. In addition, the mean duration of symptoms is similar to previous studies [17,18].…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, several reports showed that the pandemic strongly affected dental practice [17,18]. The cause of this high prevalence could be the failure to respond to the pandemic on a national basis and the insufficiency of Iraq's medical infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Estudos têm demonstrado que instrumentos utilizados durante procedimentos odontológicos como peças de mão e instrumentos ultrassônicos resultam na geração de gotículas de sangue e saliva. Consequentemente, o Sars-CoV-2 pode ser transportado por aerossóis gerados por meio dos procedimentos, bem como contaminar os instrumentos e o ambiente odontológico (11) (12). No entanto, a análise dos dados mostrou que apenas 49 (17,2%) dos dentistas paranaenses entrevistados foram infectados antes de serem vacinados, enquanto a grande maioria 183 (64,2%) não contraiu COVID-19.…”
Section: Resultsunclassified
“…An inverse trend was noted between the COVID-19 pandemic prevalence and oral health care admissions, which further increased during the second wave of the pandemic. 26,27 Research suggests that in view of the pandemic, 32.5% of the patients seeking dental care for routine dental treatments preferred teleconsultation in the present situation. However, only 18% of individuals were ready to avail dental treatment owing to the pandemic distress, since oral treatments involve aerosol procedures that can increase their risk of contracting the disease.…”
Section: Will Covid-19 Vaccination Ace Oral Health and Access To Oral...mentioning
confidence: 99%